2022
DOI: 10.1155/2022/2690871
|View full text |Cite
|
Sign up to set email alerts
|

Isometric Quadriceps Exercises for Patients with Knee Osteoarthritis: A Randomized Controlled Trial Comparing Knee Joint Position Flexion versus Extension

Abstract: Objective. To compare the effect of quadriceps isometric exercises performed in two different positions in addition to the combined physical therapy program on pain, stiffness, and physical function in patients with knee osteoarthritis (OA). Methods. A total of 30 patients with OA (age range 45 to 70 years) who were admitted to Istanbul Private Ekotom Medical Center, Department of Physical Medicine and Rehabilitation Outpatient Clinic, were included. The patients were randomly divided into two groups according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…It was found that there was a decrease in pain intensity in the intervention group of elderly patients with knee osteoarthritis. Patients with osteoarthritis of the knee experience functional limitations such as changing positions from sitting, standing and lying down, walking, climbing stairs, praying, and in more severe cases, they can cause disability, requiring assistive devices to walk (Guo et al, 2022;Sengul et al, 2022). The main clinical feature of knee osteoarthritis is pain in the movement of the knee.…”
Section: Disscussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that there was a decrease in pain intensity in the intervention group of elderly patients with knee osteoarthritis. Patients with osteoarthritis of the knee experience functional limitations such as changing positions from sitting, standing and lying down, walking, climbing stairs, praying, and in more severe cases, they can cause disability, requiring assistive devices to walk (Guo et al, 2022;Sengul et al, 2022). The main clinical feature of knee osteoarthritis is pain in the movement of the knee.…”
Section: Disscussionmentioning
confidence: 99%
“…The increase occurred after observation to control severe pain by 13 respondents and moderate pain by two respondents. There were significant differences in the Numeric Rating Scale (NRS) scores of the intervention group and the control group which showed a decrease in pain in the intervention group with a onemonth treatment time (Anwer and Alghadir, 2014;Hasan et al, 2022;Sengul et al, 2022). This is caused by changes in the length of the quadriceps femoris muscle in the knee joint, which helps stabilize the joint, decreases neuromuscular impulses, and slows axoplasmic transport, thereby reducing the muscle load on the knee joint during activities (Smithard et al, 2022).…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Latihan ini dilakukan secara statis, tanpa adanya gerakan, namun tetap terjadi kontraksi otot. Latihan ini merupakan latihan penguatan sederhana yang dapat dilakukan secara mandiri tanpa memerlukan alat bantu lain(Sengul et al, 2022). Pengukuran kekuatan otot pada m. quadriceps mengalami peningkatan setelah diberikan latihan berupa Isometric exercise.…”
unclassified